ANALISIS PERMINTAAN SOUVENIR DI PASAR SENI UBUD GIANYAR, BALI - Meilani, Diah Tantri; Negara, I Made Kusuma; Kusuma Dewi, Luh Gede Leli (Jurnal IPTA (Industri Perjalanan Wisata); Vol 5 No 2 (2017): Jurnal IPTA (Desember 2017)DO - 10.24843/IPTA.2017.v05.i02.p05, 2018)
The globalization era has changed the economic order of society such as the demand decrease of souvenirs in traditional markets because the increasing number of modern market, especially in Bali. The aim of this research is to find out variables that influence the demand of souvenirs in traditional market and hopefully can be used as a benchmark in maintaining the existence of traditional art market, increasing the demand of souvenirs , income, and increasing the number of tourist visits to Ubud traditional market, Gianyar Bali. The respondent in this study include visitors and tourists of Ubud art market. Determination of the sample in this study using purposive sampling method as much as 130 respondents. Technical data using questionnaires and interviews. This research use data analysis technique such as; of validity and reliability test, classical clinical test, determination test, multiple linear regression analysis and hypothesis test. Partially, the results showed if motivation on buying souvenir with influence equal 18,955 (2) perceived value of souvenir with influence equal 3,525, (3) consumer behavior with influence equal 20,212. Meanwhile, simultaneously showing motivation to buy souvenirs, perceived value of souvenir and consumer behavior shows the total influence 419,961. From the result of quantitative descriptive analysis, known that the most influence variables of demand analysis in Ubud art market is consumer behavior which consist of market location, cleanliness, price, parking area, infrastructure, and market hours (opening – closed hours).